Pengaruh Overconfidence Dan Representativeness Terhadap Keputusan Investasi Investor Di Pasar Modal Dengan Financial Literacy Sebagai Variabel Moderating - Nurhardika, Luhur; Widjajanti, Kesi; Indriana, Dian (Magister Manajemen STIE Bank BPD Jateng, 2025)
The aims of this research is to determine the influence of Behavioral Finance factors on investors investment decisions in the capital market. Investment decisions still involve by emotional factors, that make the investor suffer with bad return. There are several factors that are thought to influence investors irrational investment decisions including Overconfidence and Representativeness. The Financial Literacy factor is thought to be able to reduce bias in investment decision making. This research was conducted by distributing questionnaires to respondents with the criteria of investors in Semarang City who have been actively investing for at least one year. The number of research respondents was 100 respondents and data processing used SPSS 25 with MRA multiple regression analysis techniques. The results of this research state that Overconfidence and Representativeness have a significant effect on investment decisions. Financial Literacy is able to moderate the effect of Representativeness on investment decisions but cannot moderate the effect of Overconfidence on investment decisions of investors in Semarang City